The globular cluster system of NGC 1316 II. The extraordinary object SH2 - Richtler, T. (2012)
Context: SH2 has been described as an isolated HII-region, located about 6.5 south of the nucleus of NGC 1316 (Fornax A), a merger remnant in the the outskirts of the Fornax cluster of galaxies. Aims: We give a first, preliminary description of the stellar content and environment of this remarkable object. Methods: We used photometric data in the Washington system and HST photometry from the Hubble Legacy Archive for a morphological description and preliminary aperture photometry. Low-resolution spectroscopy provides radial velocities of the brightest star cluster in SH2 and a nearby intermediate-age cluster. Results: SH2 is not a normal HII-region, ionized by very young stars. It contains a multitude of star clusters with ages of approximately 108 yr. A ring-like morphology is striking. SH2 seems to be connected to an intermediate-age massive globular cluster with a similar radial velocity, which itself is the main object of a group of fainter clusters. Metallicity estimates from emission lines remain ambiguous. Conclusions: The present data do not yet allow firm conclusions about the nature or origin of SH2. It might be a dwarf galaxy that has experienced a burst of extremely clustered star formation. We may witness how globular clusters are donated to a parent galaxy.